Penggunaan Game Interaktif Wordwall dalam Evaluasi Mata Pelajaran Pendidikan Agama Islam di SDN 17 Gurun Laweh Padang - Dhillan Zalillah; Alfurqan Alfurqan (MANAZHIM, 2022)
The purpose of this study was to find out how the use of interactive wordwall in the evaluation of Islamic religious education learning activities in grade IV SD N 17 Gurun Laweh, with technological developments that continues to grow, especially in teacher education is required to be able to innovate in learning media, therefore wordwall is a one of the learning media, especially as an online that makes it easier for teachers to increase student interest in participating in evaluation activities. This study uses a descriptive qualitative approach, the data sources in this study include seven informants and documentation, the methods used in this study are observation, interviews, and documentation. Data analysis with data reduction, data presentation, and drawing conclusions. To analyze the data, the researcher used the triangulation of method which was to check again. The results of this study indicate that, SD N 17 Gurun Laweh already uses wordwall as an evaluation tool at the time of learning evaluation. Although in the use wordwall there are still obstacles in various aspects and the use wordwall makes it easier and attracts students in fun evaluation activities.